Effect of dental education on knowledge and clinical behavior of turkish dentists’ regarding oral-systemic health of geriatric patients: ORAL-SYSTEMIC HEALTH OF GERIATRIC PATIENTS - Ozan, Gunce; Yildiz, Esra; Yildiz, Sevda Ozel (Brazilian Dental Science, 2021)
Objective: The aim is to evaluate the perspectives of dentists’ clinical approaches in terms of their knowledge and education regarding oral-systemic health relation of geriatric patients with a digital survey. Materials and Methods: The demographics, oral-systemic health-related lectures in participants' dentistry education, the level of awareness of the oral-systemic health relationship, and behaviors related to clinical applications were investigated on a digital platform with 49 multiple-choice questions. The results were analyzed with the SPSS 24.0 program. Results: Of a total of 410 dentists (206 women and 204 men), 23% have doctoral and/or specialty titles. While 93.1% of dentists had taken systemic health-related lectures, 21.3% of them rated these courses as “adequate” and 49.3% as weak. 72% of the participants received medical history only at the initial appointment, while 17.9% of them received it at each appointment. Dentists more often associate diabetes and cardiovascular diseases with periodontitis, compared to the development of dental caries. Dentists who think that they should work with physicians in the treatments of geriatric patients with systemic diseases refer more patients to physicians per year (p < 0.001). Conclusions: Dentists have found the lectures on the relationship between oral-systemic health of geriatric patients in dentistry education inadequate. Besides, there is a lack of information on the effects of systemic diseases on caries development, intra-oral findings, and knowledge on treatment approaches. Dentists believe that defining a curriculum that emphasizes interdisciplinary work and organizing scientific activities in partnership with medical associations will play an important role in establishing awareness of oral-systemic health.KeywordsDental education; Dental health survey; Geriatric dentistry; Interdisciplinary communication; Oral health.